2008
DOI: 10.1007/s11103-008-9383-8
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Homeodomain-leucine Zipper II gene family: diversity and redundancy

Abstract: The Arabidopsis genome contains 10 genes belonging to the HD-Zip II family including ATHB2 and HAT2. Previous work has shown that ATHB2 is rapidly and strongly induced by light quality changes that provoke the shade avoidance response whereas HAT2 expression responds to auxin. Here, we present a genome-wide analysis of the HD-Zip II family. Phylogeny reconstruction revealed that almost all of the HD-Zip II genes can be subdivided into 4 clades (alpha-delta), each clade comprising 2-3 paralogs. Gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
209
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(214 citation statements)
references
References 42 publications
5
209
0
Order By: Relevance
“…HAT4 and PIL1 are strongly induced during shade avoidance responses to far-red light (Devlin et al, 2003). HAT4 is a member of the homeodomain Leu zipper family of transcription factors, binding DNA via the 9-bp sequence CAATNATTG (Henriksson et al, 2005;Ciarbelli et al, 2008). Analysis of multiple phytochrome-deficient mutants revealed that HAT4 expression is redundantly suppressed by PHYB and PHYE (Franklin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…HAT4 and PIL1 are strongly induced during shade avoidance responses to far-red light (Devlin et al, 2003). HAT4 is a member of the homeodomain Leu zipper family of transcription factors, binding DNA via the 9-bp sequence CAATNATTG (Henriksson et al, 2005;Ciarbelli et al, 2008). Analysis of multiple phytochrome-deficient mutants revealed that HAT4 expression is redundantly suppressed by PHYB and PHYE (Franklin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Images were taken with a Jenoptik ProgRes C10 camera mounted either on a Zeiss Axioskop 2+ microscope equipped with Nomarski optics or on a Leica MZ12 stereomicroscope. RNA extraction and quantitative reverse transcription PCR (qRT-PCR) were performed as previously described using the ACTIN 2 gene as a reference (Ciarbelli et al, 2008) and analyzed according to Pfaffl (Pfaffl, 2001). Primer sequences and Universal Probe Library (UPL) probes are given in the supplementary material Table S2.…”
Section: Phenotypic and Expression Analysesmentioning
confidence: 99%
“…Some HD-ZIP I genes not only are reported to be involved in abscisic acid and sucrose signaling pathways but are also critical to plant abiotic stress responses, embryogenesis, and cotyledon and leaf development (Himmelbach et al, 2002;Johannesson et al, 2003). The HD-ZIP II subfamily consists of 9 members (ATHB2/HAT4, ATHB4, HAT9,HAT14,HAT17,and HAT22) (Ciarbelli et al, 2008). All the 9 members possess a set of conserved cysteine molecules in and outside the LZ motif (Tron et al, 2002).…”
Section: Introductionmentioning
confidence: 99%